2016
DOI: 10.1038/srep23143
|View full text |Cite
|
Sign up to set email alerts
|

A strategy to optimize the thermoelectric performance in a spark plasma sintering process

Abstract: Spark plasma sintering (SPS) is currently widely applied to existing alloys as a means of further enhancing the alloys’ figure of merit. However, the determination of the optimal sintering condition is challenging in the SPS process. This report demonstrates a systematic way to independently optimize the Seebeck coefficient S and the ratio of electrical to thermal conductivity (σ/κ) and thus achieve the maximum figure of merit zT = S2(σ/κ)T. Sb2−xInxTe3 (x = 0–0.2) were chosen as examples to validate the metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Co-sintering can be detrimental to the thermoelectric properties, since the optimum sintering temperature and pressure vary for n-and p-type TE materials due to the difference in composition. For example, Chiu et al reported that only a temperature difference of 50 K from the optimum sintering condition can result in a drop of the overall thermoelectric properties, especially zT by 75% of the optimum value [32]. Generally, in the case of skutterudite, the difference of the sintering temperature between the p-type and the n-type is about 100 K [14], which can significantly affect the property.…”
Section: Fabrication Of the Tubular Modulementioning
confidence: 99%
“…Co-sintering can be detrimental to the thermoelectric properties, since the optimum sintering temperature and pressure vary for n-and p-type TE materials due to the difference in composition. For example, Chiu et al reported that only a temperature difference of 50 K from the optimum sintering condition can result in a drop of the overall thermoelectric properties, especially zT by 75% of the optimum value [32]. Generally, in the case of skutterudite, the difference of the sintering temperature between the p-type and the n-type is about 100 K [14], which can significantly affect the property.…”
Section: Fabrication Of the Tubular Modulementioning
confidence: 99%
“…The dominant effect of lowering thermal conductivity in nanostructuring materials is tuning the size and porosity of crystal grains78. The morphology and dimension of crystals play important roles in regulating transport of carriers and phonons910.…”
mentioning
confidence: 99%
“…The effective mean free path for grain boundary scattering is closely related to the average grain size. Tailoring the grain size to optimize the transport of phonon is a crucial strategy for high thermoelectric materials1213.…”
mentioning
confidence: 99%
“…Actually, they are also famous thermoelectric materials with high thermoelectric coefficient near room temperature (RT) for applications in waste-heat recovery, refrigeration or portable power generation, since they possess notable properties such as a prominent Seebeck effect, low thermal conductivity and high value of the carrier concentration in RT45678. The thermoelectric performance of materials is evaluated by figure of merit ZT  = ( S 2 σ / k ) T , where S is the Seebeck coefficient, σ is the electrical conductivity, k is the thermal conductivity, and T is the absolute temperature891011121314. In the past decades, many kinds of methods have been developed to improve the ZT value through modulating the parameters S , σ and k in order to improve the conversion efficiency of thermoelectric devices101315.…”
mentioning
confidence: 99%
“…The thermoelectric performance of materials is evaluated by figure of merit ZT  = ( S 2 σ / k ) T , where S is the Seebeck coefficient, σ is the electrical conductivity, k is the thermal conductivity, and T is the absolute temperature891011121314. In the past decades, many kinds of methods have been developed to improve the ZT value through modulating the parameters S , σ and k in order to improve the conversion efficiency of thermoelectric devices101315. For example, donor or acceptor impurities and other elements are doping into the alloys in order to optimize the charge carrier concentration, but they usually increase the k at the same time51617.…”
mentioning
confidence: 99%